Licochalcone A in Combination with Salicylic Acid as Fluid Based and Hydroxy-Complex 10% Cream for the Treatment of Mild Acne: A Multicenter Prospective Trial - Dall'Oglio F; Fabbrocini G; Tedeschi A; Donnarumma M; Chiodini P; Micali G (Dove Medical Press, 2020)
Federica Dall’Oglio,1 Gabriella Fabbrocini,2 Aurora Tedeschi,1 Marianna Donnarumma,2 Paolo Chiodini,3 Giuseppe Micali1 1Dermatology Clinic, University of Catania, Catania, Italy; 2Section of Dermatology, Department of Clinical Medicine and Surgery, University Federico II of Naples, Naples, Italy; 3Medical Statistics Unit, University of Campania “Luigi Vanvitelli”, Naples, ItalyCorrespondence: Giuseppe MicaliDermatology Clinic, University of Catania, A.O.U. Policlinico -Vittorio Emanuele, via Santa Sofia, 78, Catania 95123, ItalyTel +39 095321705Fax +39 0953782425Email cldermct@gmail.comPurpose: Topical cosmetic agents if correctly prescribed and used may improve outcomes in acne therapy. The aim of this study was to assess the efficacy and tolerability of a new daily cosmetic regimen in the treatment of mild facial acne.Patients and methods: A multicenter, prospective, observational, clinical study was conducted on 91 adult patients with mild acne. Subjects were instructed to apply a fluid containing Licochalcone A/Salicylic acid/L-Carnitine in the morning and a cream with Licochalcone A/Hydroxy-Complex 10% at bedtime for 8 weeks. The efficacy was clinically evaluated by Global Acne Grading System (GAGS) score and by comedones/papules lesions count and by instrumental assessment (SebutapeTMand Reveal Photo Imager/VISIA-CR™ imaging) at baseline, at 4 and 8 weeks.Results: At 4 weeks a statistically significant reduction from baseline of GAGSwas observed. In addition, the mean total count of comedones and papules was significantly reduced by 41% and 45%, respectively, from baseline along with a significant reduction of mean sebum of 47%. At 8 weeks, a further statistically significant reduction from baseline of GAGS, total count of comedones and papules (64% and 71%, respectively), along with an additional sebum reduction of about 52% was also recorded.Conclusion: Our results suggest that the daily regimen based on Licochalcone A with Salicylic acid/L-Carnitine as fluid or with Hydroxy-Complex 10% as cream represent an interesting cosmetic approach for treating mild acne.Keywords: mild acne, topical cosmetic, licochalcone A, salicylic acid, hydroxyl-complex